Autonomous language learning through a mobile application: a user evaluation of the busuu app. Issue 8 (2nd November 2018) - Rosell-Aguilar, Fernando
ABSTRACT: Studies into the use of mobile applications (apps) for language learning have found positive results on language improvement and learner engagement, but they have mostly focused on small samples of learners using apps that were selected by a researcher/educator rather than on learners using apps of their own choice. This article presents the results of a large-scale survey ( n = 4095) into the use of one of the most popular language learning apps in the market: the busuu mobile app (over 60 million registered users). Data were collected through an online questionnaire with 30 items. The survey was distributed both in English and in Spanish. The results provide a profile of busuu app users, show patterns of use, and what app features learners find most valuable for language learning. Most users are at beginner level and learn for personal interest. They find the app has helped them improve their knowledge of the language they are learning, with vocabulary as the main area of improvement. The high expectations from users and the fact that a third of respondents use busuu as their only language learning source suggest that a large proportion of users consider apps a reliable tool for language learning.